2005
DOI: 10.1099/mic.0.27750-0
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic behaviour of microtubules and their contributions to hyphal tip growth in Aspergillus nidulans

Abstract: Creating and maintaining cell polarity are complex processes that are not fully understood. Fungal hyphal tip growth is a highly polarized and dynamic process involving both F-actin and microtubules (MTs), but the behaviour and roles of the latter are unclear. To address this issue, MT dynamics and subunit distribution were analysed in a strain of Aspergillus nidulans expressing GFP-a-tubulin. Apical MTs are the most dynamic, the bulk of which move tipwards from multiple subapical spindle pole bodies, the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 82 publications
(94 reference statements)
1
37
1
1
Order By: Relevance
“…All GCPs localized to septa, but the fluorescence of GCPD-GCPF was barely above background levels. These data are consistent with previous findings that the SPB is the major MTOC throughout the cell cycle (Horio and Oakley, 2005;Sampson and Heath, 2005) and with the finding that microtubules might sometimes grow from septa (Konzack et al, 2005). Konzack and colleagues have suggested that an MTOC might be present at the hyphal apex, on the basis of observations of the movement of a GFP-kinesin-like protein under control of an inducible promoter (Konzack et al, 2005); however, other, more direct, studies (Horio and Oakley, 2005;Sampson and Heath, 2005) have not revealed an apical MTOC and we find no localization of GCPs at the apex.…”
Section: Gcp2-gcp6 Homologs Exist In a Nidulanssupporting
confidence: 83%
“…All GCPs localized to septa, but the fluorescence of GCPD-GCPF was barely above background levels. These data are consistent with previous findings that the SPB is the major MTOC throughout the cell cycle (Horio and Oakley, 2005;Sampson and Heath, 2005) and with the finding that microtubules might sometimes grow from septa (Konzack et al, 2005). Konzack and colleagues have suggested that an MTOC might be present at the hyphal apex, on the basis of observations of the movement of a GFP-kinesin-like protein under control of an inducible promoter (Konzack et al, 2005); however, other, more direct, studies (Horio and Oakley, 2005;Sampson and Heath, 2005) have not revealed an apical MTOC and we find no localization of GCPs at the apex.…”
Section: Gcp2-gcp6 Homologs Exist In a Nidulanssupporting
confidence: 83%
“…Filamentous actin arrays are concentrated in areas of active cell extension and cell wall deposition (Heath 1990b(Heath , 1995Heath et al 2000). In Aspergillus nidulans, cytoplasmic actin arrays have documented roles in hyphal extension and in morphogenesis (Harris et al 1994;Torralba et al 1998;Sampson and Heath 2005), septation (Momany and Hamer 1997), and mitochondrial motility (Suelmann and Fischer 2000a). A class I myosin is essential in A. nidulans and is enriched at hyphal tips (McGoldrick et al 1995).…”
Section: Introductionmentioning
confidence: 98%
“…They can modulate second messenger signalling pathways, providing intracellular trafficking, and organizing communication networks between inter-and intracellular components Heasman & Ridley, 2008;Sampson & Heath, 2005;Xiang & Plamann, 2003). The actin cytoskeleton is involved in many processes in eukaryotic cells, including interaction with a wide variety of actin-binding proteins such as the actin-capping proteins, the actin filament nucleators, and the actin crosslinking proteins (Santella et al, 2008;Schafer & Schroer, 1999;Schroer et al, 1994;Sjoblom et al, 2008).…”
Section: Introductionmentioning
confidence: 99%